2018
DOI: 10.1016/j.omtn.2018.09.026
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA GAS5 Reverses EMT and Tumor Stem Cell-Mediated Gemcitabine Resistance and Metastasis by Targeting miR-221/SOCS3 in Pancreatic Cancer

Abstract: Dysregulated long noncoding RNAs (lncRNAs) and microRNAs (miRNAs) mediating chemotherapeutic drug effects and metastasis in pancreatic cancer (PC) are key reasons for the poor prognosis of this disease. lncRNA growth arrest-specific 5 (GAS5) is reported to be a tumor suppressor in multiple cancers. However, the functions of GAS5 and its related miRNAs in PC are poorly understood. This study explored the potential functions and mechanisms of GAS5 in PC gemcitabine resistance and metastasis. The results show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
112
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(114 citation statements)
references
References 44 publications
1
112
0
Order By: Relevance
“…the proliferation, invasion, migration, epithelial mesenchymal transition (EMT), and radiation resistance of cancer cells [101][102][103]. LncRNA GAS5-AS1 is the antisense RNA of GAS5, and its downregulation is closely related to the TNM stage, lymph node metastasis, and prognosis of tumors, such as NSCLC and liver cancer [104,105].…”
Section: Regulation Of M6a Modifications By Noncoding Rnasmentioning
confidence: 99%
“…the proliferation, invasion, migration, epithelial mesenchymal transition (EMT), and radiation resistance of cancer cells [101][102][103]. LncRNA GAS5-AS1 is the antisense RNA of GAS5, and its downregulation is closely related to the TNM stage, lymph node metastasis, and prognosis of tumors, such as NSCLC and liver cancer [104,105].…”
Section: Regulation Of M6a Modifications By Noncoding Rnasmentioning
confidence: 99%
“…Studies have shown that GAS5 inhibits drug resistance in PDAC by negative regulation of miR-181c-5p and reducing the inactivation of the Hippo signal transduction pathway (61). Overexpression of GAS5 inhibits PDAC cell proliferation, migration and gemcitabine resistance through miR-221/suppressor of cytokine signaling 3 (SOCS3) mediated EMT and tumor CSCs (62).…”
Section: Gas5mentioning
confidence: 99%
“…Previous studies validated that SOCS3 expression is downregulated in cancer tissues, including pancreatic cancer, colorectal cancer, lung cancer, bladder cancer, and breast cancer . SOCS3 overexpression has an anti‐proliferative and anti‐metastatic effect in cancer . Previous studies have found that when a cytokine or a growth factor binds to an intracellular receptor as a ligand, the receptor can form a heterodimer and phosphorylate the JAK kinase.…”
Section: Discussionmentioning
confidence: 92%
“…[32][33][34][35][36] SOCS3 overexpression has an anti-proliferative and anti-metastatic effect in cancer. 37,38 Previous studies have found that when a cytokine or a growth factor binds to an intracellular receptor as a ligand, the receptor can form a heterodimer and phosphorylate the JAK kinase. Activated JAK can phosphorylate the tyrosine residue of STAT and activated STAT is separated from the receptor complex, forms a dimer, and is translocated from the cytoplasm to the nucleus, where it acts on specific DNA fragments and regulates gene transcription and expression.…”
Section: Discussionmentioning
confidence: 99%